2019
DOI: 10.1016/s2214-109x(19)30254-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of report cards on the coverage of maternal and neonatal health care: a factorial, cluster-randomised controlled trial in Uttar Pradesh, India

Abstract: Background Report cards are a prominent strategy to increase the ability of citizens to express their view, improve public accountability, and foster community participation in the provision of health services in low-income and middle-income countries. In India, social accountability interventions that incorporate report cards and community meetings have been implemented at scale, attracting considerable policy attention, but there is little evidence on their effectiveness in improving health. We aimed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…For example, several programmes entailed health facility-led efforts to engage communities in expressing their priorities regarding quality of care; some of these had an explicit health facility accountability component 35 37 42 85–88. Other health sector programmes aimed to create change in the way organisations operate, including health facilities89–92; health and allied professional associations and other organisational stakeholders in SRH, including law enforcement93–95; schools96; and factories 97. For example, a school-based programme in Uganda supported teachers to exercise respectful leadership, such as through the practice of non-punitive discipline 96…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, several programmes entailed health facility-led efforts to engage communities in expressing their priorities regarding quality of care; some of these had an explicit health facility accountability component 35 37 42 85–88. Other health sector programmes aimed to create change in the way organisations operate, including health facilities89–92; health and allied professional associations and other organisational stakeholders in SRH, including law enforcement93–95; schools96; and factories 97. For example, a school-based programme in Uganda supported teachers to exercise respectful leadership, such as through the practice of non-punitive discipline 96…”
Section: Resultsmentioning
confidence: 99%
“…Many of the health facility-focused programmes aimed to foster the provision of respectful (maternity) care, such as programmes aiming to improve communication between providers and patients and their families; to ensure that providers do not employ condescending, demeaning or discriminatory language; and to support community monitoring of health facilities to prevent and document disrespect 91 92 101 102. To effect such change, some programmes created mechanisms of communication between health providers/facilities and communities to increase health system responsiveness,35 44 89 103 or introduced a birth companion or care navigator to change the dynamics of power between the patient and providers 104…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment was set up to test the importance of report card information versus creating an interface between providers and community members. Similarly, a report card study in India (Fabbri et al, 2019) (45 clinics in each of three treatment arms) also found no effected of any of the interventions on the targeted outcome of maternal care. That study was set up to test the importance of discussing the outcomes of the report card in provider groups, community groups or both.…”
mentioning
confidence: 93%